Mechanical Properties of Oil Palm Fibre-Thermoset Composites - Mohamed Yusoff, Mohd Zuhri (2009)
Over the last decade, polymers reinforced with natural fibres composites have been getting an increasing attention from the academic world and various industries. Natural fibres are prospective reinforcing materials and their usage until now has been more traditional than technical. The attractive features of natural fibres are their low cost, lightweight, high specific modulus, renewability and biodegradability. Oil palm empty fruit bunches (OPEFB) are readily available in large quantities in palm oil mills. The fact is oil palm fibre (OPF) can be obtained directly from natural resource, cheap and also has advantages due to their renewable nature, low cost, and easy availability. This study was aim to determine the tensile and flexural properties of oil palm fibre-thermoset composites. Oil palm fibre/phenol formaldehyde (OPF/PF) composites and oil palm fibre reinforced epoxy (OPF/Epoxy) composites were fabricated to carry out the determination of mechanical properties. The composites were prepared by volume fraction of 40%, 50% and 60% for OPF/PF while for OPF/epoxy were 5%, 10%, 15% and 20%. Composites were cut based on the ASTM D638 for tensile testing and ASTM D790 flexural testing. The testing was conducted on a Universal Testing Machine while the interfacial adhesion between fibre and matrix were observed using the scanning electron microscopy (SEM). Results from tensile and flexural tests of OPF/PF composites showed an increasing trend of tensile and flexural strengths as the volume fraction of fibre was increased. From the scattered values, it is found that the highest tensile and flexural strengths for OPF/PF composites were obtained at 60% volume fraction, in average. The results of tensile and flexural tests for OPF/Epoxy composites showed that by the addition of fibre content, the tensile and flexural strength was decreased compared to pure epoxy resin (0% fibre). It has been notice that to obtain the optimum tensile and flexural properties was found at the volume fraction of 5%. It is also found that the dispersion of fibre and interfacial adhesion between fibre – matrix can affect the mechanical properties of the composites.